Fetomaternal outcomes of hospitalized hypertensive gravida in Shaqra General Hospital: a retrospective study - Abalos, Russel; Ellasus, Rosanta; Gutierrez, John Mark (International Journal of Advanced Nursing Studies, 2015)
Background: Elevation of blood pressure during pregnancy can adversely affect both fetal and maternal outcomes. Other maternal and fetal complications may also arise which may result to maternal and fetal mortality.Objective: This study aimed to determine the fetal and maternal outcomes of hospitalized pregnant clients with hypertension.Methods: This 6-year retrospective research design was carried out in Shaqra General Hospital between January 2008 and November 2013. Following approval by the hospital research ethics committee and hospital administrators, hospital records were reviewed and examined using guide checklist. Universal sampling was applied totaling to 56 evaluable cases of pregnant women with hypertension.Results: Of 56 cases studied, year 2008 to 2013 had the most frequency of hypertensive mothers. Most women are in middle adulthood stage with age 25 years old and above, had more than one pregnancy (multigravida) and more than one viable pregnancy (multipara). Fetal outcome resulted to high number of babies who were term, appropriate for gestational age, with good Apgar score, no birth defect but high frequency of neonatal intensive care unit (NICU) admissions. Maternal outcome recorded no maternal deaths; however, 4% maternal complications (i.e., post-partum hemorrhage and HELLP syndrome) and more caesarean section deliveries were observed.Conclusion: Good Apgar score and absence of birth defects is associated with higher frequency of roomed-in babies and less NICU admissions. There were lesser complications to mothers who had more than one pregnancy. There were more NICU admissions from caesarean section deliveries.